Unseen barriers: addressing racism in European healthcare - Amel Filali; Lindsay Osei; Nicolas Vignier (International Journal for Equity in Health)
Abstract Structural racism in healthcare is largely unexplored in the European context. When studied, racism is explored as an individual opinion and not as a structural problem. Very little data exists for European populations belonging to minority groups. Most of the data available focus on migration and healthcare. The increased risk of infectious diseases among migrant populations in Europe is well documented, linked to the epidemiology of their countries of origin, migratory pathways and vulnerabilities acquired on the European continent. However, the impact of racism on access to health care for racially marginalised migrants remains underexplored compared to other barriers. Most studies on the health of different categories of migrants focus on migration status as a determinant, without addressing the effects of racism in the context of migration. It is therefore crucial to generate contextual data in Europe to study the potential existence of these biases and their influence on the management of health care of minorities.